Roles and functions of SARS-CoV-2 proteins in host immune evasion - Rashid, Farooq; Xie, Zhixun; Suleman, Muhammad; Shah, Abdullah; Khan, Suliman; Luo, Sisi (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) evades the host immune system through a variety of regulatory mechanisms. The genome of SARS-CoV-2 encodes 16 non-structural proteins (NSPs), four structural proteins, and nine accessory proteins that play indispensable roles to suppress the production and signaling of type I and III interferons (IFNs). In this review, we discussed the functions and the underlying mechanisms of different proteins of SARS-CoV-2 that evade the host immune system by suppressing the IFN-β production and TANK-binding kinase 1 (TBK1)/interferon regulatory factor 3 (IRF3)/signal transducer and activator of transcription (STAT)1 and STAT2 phosphorylation. We also described different viral proteins inhibiting the nuclear translocation of IRF3, nuclear factor-κB (NF-κB), and STATs. To date, the following proteins of SARS-CoV-2 including NSP1, NSP6, NSP8, NSP12, NSP13, NSP14, NSP15, open reading frame (ORF)3a, ORF6, ORF8, ORF9b, ORF10, and Membrane (M) protein have been well studied. However, the detailed mechanisms of immune evasion by NSP5, ORF3b, ORF9c, and Nucleocapsid (N) proteins are not well elucidated. Additionally, we also elaborated the perspectives of SARS-CoV-2 proteins.